汉语“经常”“常常” “往往”与印尼语“SERING”的对比分析 COMPARISON OF “JINGCHANG” “CHANGCHANG” AND “WANGWANG” IN MANDARIN WITH THE WORD “SERING” IN INDONESIAN - Sinar Anwar (Journal of Language, Literature and Teaching, 2021)
The words "jingchang", "changchang" and "wangwang" have the same meaning when translated into Indonesian, namely "often". This is because language is unique and universal, therefore, this study aims to describe the similarities and differences between the words "jingchang", "changchang" and "wangwang" in Mandarin with the word "often" in Indonesian.The design of this research method is descriptive qualitative research. The data collection technique was carried out with documentation techniques and the data sources of this research were 4 Chinese books, 9 Chinese journals and 4 Indonesian books. The theory used is the theory of the universality of language and the uniqueness of language, as well as the theory of contrastive analysis to examine the similarities and differences of the three words in terms of meaning, use and form.The results of the analysis show that there are 6 similarities and 13 differences in the words "jingchang", "changchang" and "wangwang" in Mandarin with the word "often" in Indonesian.Key words: Jingchang, Changchang, Wangwang, Sering, Comparison.